2015
DOI: 10.1002/rcm.7145
|View full text |Cite
|
Sign up to set email alerts
|

Variability of higher trophic level stable isotope data in space and time - a case study in a marine ecosystem

Abstract: Seasonal differences in the relative position of species or species groups in the C-N isotope space suggest changes in the utilisation of planktonic vs. benthic trophic pathways, indicating flexible foraging strategies in response to variable environmental conditions. These seasonal differences should be taken into account when analysing higher trophic level feeding ecology with stable isotope analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…Annual and spatial variation in some prey species has been previously described by Quillfeldt et al. (), and this may have affected our results. Specifically, year differences in the isotopic baseline could have precluded us from finding a relationship between environmental conditions and the penguins' isotopic values.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Annual and spatial variation in some prey species has been previously described by Quillfeldt et al. (), and this may have affected our results. Specifically, year differences in the isotopic baseline could have precluded us from finding a relationship between environmental conditions and the penguins' isotopic values.…”
Section: Discussionmentioning
confidence: 63%
“…We therefore cannot assess whether and how these isotopic values differed among years and over the broad spatial scale utilized by SRP during the prebreeding and premolt periods (Dehnhard et al 2011;Ratcliffe et al 2014). Annual and spatial variation in some prey species has been previously described by Quillfeldt et al (2015), and this may have affected our results. Specifically, year differences in the isotopic baseline could have precluded us from finding a relationship between environmental conditions and the penguins' isotopic values.…”
Section: Effects Of Environmental Variability On Stable Isotopesmentioning
confidence: 94%
“…However, the δ 13 C and δ 15 N values of top consumers integrate those of multiple prey (fish and squid) and may not necessarily reflect the lack of such variation at the base of the food web. Few previous studies have incorporated data on temporal variation (within and between years) in δ 13 C and δ 15 N values (but see Quillfeldt et al and the North Atlantic .…”
Section: Discussionmentioning
confidence: 99%
“…), although this is potentially an important reason for variation between top consumers of different species or populations in pelagic ecosystems of the Southern Ocean, and the North Atlantic . Several authors suggested that overall variation in stable isotope values measured in predator tissues is more likely to be related to variation in their diets and foraging distributions, but the temporal shifts and biogeographical trends in baseline isotope ratios should be considered in order to avoid misinterpretations in future studies, as suggested by Quillfeldt et al . Baseline and lower trophic level organisms may show substantial spatiotemporal isotopic heterogeneity and local enrichment in 13 C in phytoplankton during periods of elevated primary productivity will influence the isotopic values of upper trophic level organisms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation